Bi‐atrial characterization of the electrical substrate in patients with atrial fibrillation. Issue 6 (23rd April 2022) - Giorgios, Tsitsinakis; Antonio, Frontera; Limite, Luca Rosario; Felicia, Lipartiti; Zweiker, David; Cireddu, Manuela; Vlachos, Kostantinos; Hadjis, Alexios; D'Angelo, Giuseppe; Baratto, Francesca; Bisceglia, Caterina; Vergara, Pasquale; et al.
Abstract: Background: Little is known regarding the characterization of electrical substrate in both atria in patients with atrial fibrillation (AF). Methods: Eight consecutive patients undergoing AF ablation (five paroxysmal, three persistent) underwent electrical substrate characterization during sinus rhythm. Mapping of the left (LA) and right atrium (RA) was performed with the use of the HD Grid catheter (Abbott). Bipolar voltage maps were analyzed to search for low voltage areas (LVA), the following electrophysiological phenomena were assessed: (1) slow conduction corridors, and (2) lines of block. EGMs were characterized to search for fractionation. Electrical characteristics were compared between atria and between paroxysmal versus persistent AF patients. Results: In the RA, LVAs were present in 60% of patients with paroxysmal AF and 100% of patients with persistent AF. In the LA, LVAs were present in 40% of patients with paroxysmal AF and 66% of patients with persistent AF. The areas of LVA in the RA and LA were 4.8±7.3 cm 2 and 7.8±13.6 cm 2 in patients with paroxysmal AF versus 11.7±3.0 cm 2 and 2.1±1.8 cm 2 in patients with persistent AF. In the RA, slow conduction corridors were present in 40.0% (paroxysmal AF) versus 66.7% (persistent AF) whereas in the LA, slow conduction corridors occurred in 20.0% versus 33.3% respectively (p = ns). EGM analysis showed more fractionation in persistent AF patients than paroxysmal (RA: persistent AF 10.8 vs. paroxysmal AF 4.7%, p  = .036, LA: 10.3 vs. 4.1%, p  = .108). Conclusion: Bi‐atrial involvement is present in patients with paroxysmal and persistent AF. This is expressed by low voltage areas and slow conduction corridors whose extension progresses as the arrhythmia becomes persistent. This electrophysiological substrate demonstrates the important interplay with the pulmonary vein triggers to constitute the substrate for persistent arrhythmia.